FAKTOR YANG MEMPENGARUHI AKSEPTOR KB INDOPLANT TERHADAP KONTROL ULANG DI PUSKESMAS TANJUNG BERINGIN .: Factors Affecting Indoplant KB Acceptors on Re-Control in Health Center Tanjung Beringin - Arnof Yerni (LPPM - STIKES Pemkab Jombang, 2020)
Indoplant as one of the methods of contraception under the skin, is officially used in several countries including Indonesia and is quickly accepted by the public and is one of the programmed methods of contraception. However, there are still many acceptors who do not carry out re-control after installation. This study aims to determine the factors that influence the Indoplant acceptors in carrying out re-control at TanjungBerigin Health Center in Langkat Regency in 2018. This study uses a descriptive design with cross-sectional approach. The population in this study were all indoplant acceptors after 13 months installation at Tanjung Beringin Health Center, as many as 68 people and the sampling technique was total sampling .The result of univariate analysis was the highest age of respondents> = 0.05) found the effect of age on the re-contro (p-value = 1000) and the influence of education (p-value = 0.023) and the influence of parity (p-value = 0.034) and the influence of knowledge (p-value = 0.015).a35 years 37 people (54.4%) higher education 42 people (61.8%) high parity 41 people (60.3%), high knowledge 39 people (57.4%) and those who re-controlling 53 people (77.9%). While the results of the bivariate analysis using the chi square test (95% CI and Based on the results of the study it is expected that health workers, especially midwives, can provide counseling or complete information about indoplant, especially the implementation of re-control. Keywords: Indoplant acceptors, re-control